Evaluation of dielectric breakdown of BaTiO3 by novel indentation method. Issue 13 (October 2022) - Gehringer, Maximilian; Bolat, Rizabek; Isaia, Daniel; Rödel, Jürgen; Fulanović, Lovro
Abstract: Succinct evaluation of dielectric breakdown strength of dielectric materials has been hampered by extrinsic parameters like size/thickness dependence, electrode configuration, and defect concentration which all mask the materials' intrinsic value. A novel indentation method to prepare arch-shaped indents on the surface of BaTiO3 green stacks has been developed to overcome this problem. Utilizing this method enables simple and reliable sample preparation for investigation of dielectric breakdown behavior. Theoretical and experimental investigations reveal vanishing electrode edge effects governed by the improved distribution of electric field due to the arch-shaped indents. Thus, the novel indentation method bears advantages compared to measuring DBS of disk-shaped samples and allows for narrowing influences of extrinsic parameters. By obtaining breakdown channels close to the center of the indent, this technique additionally features the possibility of localizing the breakdown event.